Retracted-Enhanced X-Ray Absorption Property of Gold-Doped Single Wall Carbon Nanotube - Alimin Alimin; Narsito Narsito; Indriana Kartini; Sri Juari Santosa (Universitas Gadjah Mada, 2015)
Enhanced X-ray absorption property of single wall carbon nanotube (SWCNT) through gold (Au) doping (Au@SWCNT) has been studied. Mass attenuation coefficient of SWCNT increased 5.2-fold after Au doping treatment. The use of ethanol in the liquid phase adsorption could produce Au nanoparticles as confirmed by the X-ray Diffraction (XRD) patterns. The possibility of gold nanoparticles encapsulated in the internal tube space of SWCNT was observed by transmission electron microscope technique. A significant decrease of nitrogen uptakes and upshifts of Radial Breathing Mode (RBM) of Au@SWCNT specimen suggest that the nanoparticles might be encapsulated in the internal tube spaces of the nanotube. In addition, a decrease intensity of XRD pattern of Au@SWCNT at around 2θ ≈ 2.6° supports the suggestion that Au nanoparticles are really encapsulated into SWCNT.